2019
DOI: 10.1016/j.enbuild.2019.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of a high-efficiency dew-point evaporative cooler

Abstract: This paper investigated the cooling performance of a high-efficiency dew-point evaporative cooler with optimised air and water flow arrangement using the combined experimental and numerical simulation method. The experimental results showed that the wet-bulb efficiency of the dew-point evaporative cooler was increased by 29.3% and COP was increased by 34.6%, compared to the existing commercial dew point air cooler of the same capacity. An improved two-dimensional, multi-factor engaged numerical model which can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…In this study, the researchers found the optimal channel length and working ratio for different scenarios. Liu et al [35] also researched the optimized DPIEC in terms of water flow arrangement. They used experimental and numerical methods to analyze the exchanger.…”
Section: Optimization the Dpiecmentioning
confidence: 99%
“…In this study, the researchers found the optimal channel length and working ratio for different scenarios. Liu et al [35] also researched the optimized DPIEC in terms of water flow arrangement. They used experimental and numerical methods to analyze the exchanger.…”
Section: Optimization the Dpiecmentioning
confidence: 99%
“…1 = −5800.2205, 2 = 1.3914993, 3 = −0.04860239, 4 = 4.1764769 × 10 −5 , 5 = −1.4452093 × 10 −8 , a 6 = 6.5459673, = 101325 . The convective mass transfer coefficient and the convective heat transfer coefficient in the wet channel are associated by the Lewis number (Liu et al, 2019).…”
Section: Counter-flow Dew Point Evaporative Cooling Modelmentioning
confidence: 99%
“…Liu et.al [1] investigated experimentally and theoretically the refrigeration behaviour of a highly efficient dew point evaporative cooler using most effective air and water flow arrangements. Different results obtained from the experiments reported the improvement of 29.3% in the cooler wet bulb efficiency.…”
Section: Experimental Research Of Dew Point Coolersmentioning
confidence: 99%